Inventarisasi Tumbuhan Sumber Pakan Lebah Madu Apis mellifera di Desa Idam Dehe Kecamatan Jailolo, Kabupaten Halmahera Barat - Nadira Irwan; Abdul Kadir Kamaluddin; Asiah Salatalohy; Siti Nurjannah (Prodi Kehutanan Universitas Khairun, 2023)
Apis mellifera (Superior bee) is the main type of honey bee cultivated in many countries, including Indonesia, one of which is in Idam Dehe Village. Honey bees are insects that use flowering plants as a source of food and are also known as insects that produce useful products. The most important factor that affects the success of honey bee cultivation is feed (nectar or pollen), so this study aims to inventory and analyze the density, frequency of important value indices in each type of plant which is a source of honey bee feed in Idam Dehe Village. This research was conducted in June - October 2022. The research method used is the plotted path method with a sampling intensity of 10%. The example tile is created as many as 40 tiles. The plots are placed on 4 lanes with a distance between plots of 50 m. Sample plot sizes of 2m × 2m, 5m × 5m, 10m × 10m and 20m × 20m. Data analysis using the formulas INP= KR+FR (for seedlings and saplings), INP= KR+FR+DR (for poles and trees). The results of the study on 4 paths with a sample plot of 40 plots, found 17 types of plants that are the source of feed for honey bees Apis mellifera with a total number of individuals 237 individuals and 14 families, which are dominated by the Arecaceae family, namely Cocos nucifera and Arenga pinnata with a total of 49 individuals at all growth rates. The results of the calculation of INP values showed that Mimosa pudica had the highest INP value at the seedling level (56.96), Piper aduncum at the stake level (31.82), as well as at the pole and tree level the highest INP value at the Cocos nucifera type was 96.22 at the pole level and 72.84 at the tree level.